I have to prove the following: $$[\sinh(a\tau'')-\sinh(a\tau')-ia\epsilon]^2-[\cosh(a\tau'')-\cosh(a\tau')]^2=4[\sinh(\frac{a}{2}(\tau''\tau')-i\epsilon)]^2$$

we know that:

$a$ is a real positive number

$\epsilon\rightarrow0$, so $\cosh(i\epsilon)=1$, and $\sinh(i\epsilon)=i\epsilon$

I have tried using the trigonometric formulas:



but I couldn't prove it. Could you please help me by giving the solution or hints? Thank you for your time.


Quite simple: start from the addition formulae: $$\begin{cases}\sinh(a+b)=\sinh a\cosh b+\sinh b\cosh a\\ \sinh(a-b)=\sinh a\cosh b-\sinh b\cosh \end{cases}$$ whence $\,2\sinh b\cosh a=\sinh(a+b)-\sinh(a-b)$.

Now set $A=a+b$, $\,B=a-b$, which is equivalent to $\,a=\dfrac{a+b}2,\enspace b=\dfrac{A-B}2$, and you get the first factorisation formula.

Smae method for the second formula, starting from the addition formulae for $\cosh$.

  • $\begingroup$ Sorry, perhaps I did not explain it well. I need to prove the first equality, not the trigonometric formulae. $\endgroup$ – Fischer Jun 11 '15 at 13:17

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.